Promoting employee ownership: a look at the states. Issue 3 (9th December 2019) - Wiefek, Nancy; Rosen, Corey; Garbinsky, Timothy
Abstract : Purpose: Close to half of all privately held companies in the USA are owned by baby boomers, meaning 2.7m American businesses are owned by someone age 55 or older. In the coming decades, all of these businesses will either change owners or disappear. The median state has 34, 000 businesses approaching an ownership transition. The effects of this generational shift will be felt in cities, small towns and rural areas. At the same time, state governments are struggling with the challenge of preserving jobs and stimulating local economies buffeted by larger economic trends. States currently spend an estimated 45bn to 70bn a year on efforts to attract and retain jobs. If even a fraction of these exiting owners pursued an Employee Stock Ownership Plan (ESOP) as their business exit strategy, the potential positive impact on workers, communities and state economies would be substantial. Yet, many business owners are not even aware of ESOPs as an option. In light of this knowledge gap, many of these businesses will instead shut down or sell to outside investors who may not be interested in preserving and growing local jobs. This paper aims to discuss these issues. Design/methodology/approach: Review of state information and statistics on employee ownership. Findings: Currently, there are around 6, 660 ESOPs in the USA holding total assets of nearly 1.4 trillion. These plans cover 14.2m participants. The Midwest is home to the greatest number of ESOPs, followed by the South. There is a least one ESOP headquartered in 4, 131 distinct zip codes. Practical implications: In order to increase the effectiveness and penetration of local outreach and education, states can: create an office of employee ownership with a dedicated staff person. The office could exist within a state agency or as a nonprofit receiving state funding; provide grants to one or more nonprofits to run an outreach program; hold seminars statewide in conjunction with professional, business, and trade publications and organizations; publish and disseminate brochures and other material; and work with the media to encourage stories on local ESOP companies. In order to promote ESOPs as an attractive alternative to private equity, outside competitors, and other potential purchasers of the business, ESOP outreach should: focus on business owners who are approaching retirement or a liquidity event, as opposed to start-ups or businesses who are interested in progressive management. Focus on the human side and emotional impact of employee ownership. Videos and other personal testimonials contrasting the storylines of a company that becomes employee-owned vs one that becomes owned by an outside investor can be powerful. Take advantage of the ESOP community by facilitating peer-to-peer connections, where company leaders talk with their peers who have sold to an ESOP. These connections are usually fostered based on location or industry. Take care to ensure that the center is seen as providing objective information as opposed to being perceived as trying to "sell" owners on the idea. Originality/value: This is the first published review of ESOPs in the states.